Discovery of novel diarylamides as orally active diuretics targeting urea transporters - Shun Zhang; Yan Zhao; Shuyuan Wang; Min Li; Yue Xu; Jianhua Ran; Xiaoqiang Geng; Jinzhao He; Jia Meng; Guangying Shao; Hong Zhou; Zemei Ge; et al. (Elsevier, 2021)
Urea transporters (UT) play a vital role in the mechanism of urine concentration and are recognized as novel targets for the development of salt-sparing diuretics. Thus, UT inhibitors are promising for development as novel diuretics. In the present study, a novel UT inhibitor with a diarylamide scaffold was discovered by high-throughput screening. Optimization of the inhibitor led to the identification of a promising preclinical candidate, N-[4-(acetylamino)phenyl]-5-nitrofuran-2-carboxamide (1H), with excellent in vitro UT inhibitory activity at the submicromolar level. The half maximal inhibitory concentrations of 1H against UT-B in mouse, rat, and human erythrocyte were 1.60, 0.64, and 0.13 μmol/L, respectively. Further investigation suggested that 8 μmol/L 1H more powerfully inhibited UT-A1 at a rate of 86.8% than UT-B at a rate of 73.9% in MDCK cell models. Most interestingly, we found for the first time that oral administration of 1H at a dose of 100 mg/kg showed superior diuretic effect in vivo without causing electrolyte imbalance in rats. Additionally, 1H did not exhibit apparent toxicity in vivo and in vitro, and possessed favorable pharmacokinetic characteristics. 1H shows promise as a novel diuretic to treat hyponatremia accompanied with volume expansion and may cause few side effects.